Strategi Komunikasi Bawaslu Kota Bima Dalam Upaya Pencegahan Pelanggaran Kampanye Pada Pemilu Legislatif Tahun 2024 - Rijkad Omar Rijkad Omar Dylian; Darmansyah Darmansyah; Azwar Subandi (Universitas Muhammadiyah Mataram, 2024)
The Communication Strategy of the Bima City Bawaslu is one of the keys to preventing campaign violations. This study aims to determine the communication strategy of the Bima City Bawaslu in an effort to prevent campaign violations in the 2024 legislative elections and to determine the factors that influence the implementation of the Bima City Bawaslu communication strategy. The research method used is qualitative with a descriptive analysis approach. Data were obtained through interviews and literature studies. The results of the study show that the communication strategy of the Bima City Bawaslu in an effort to prevent campaign violations has four aspects. The first aspect determines the target of communication, the second aspect selects communication media, the third aspect determines and conveys communication messages, the fourth aspect is the role of communicators in communication and shows that the factors that influence the implementation of the Bima City Bawaslu communication strategy are economic factors and natural resource factors.